Anti-elastase, anti-collagenase, and anti-hyaluronidase activities of Aloe barbadensis gel extract: In vitro and molecular docking studies - Rittipun Rungruang, Wittawat Ratanathavorn, Nattaporn Boohuad, Vanarat Phakeenuya, Napassorn Peasura, Tasanee Panichakul (Journal of Applied Pharmaceutical Science, 2025)
Aloe barbadensis gel is widely recognized for its wound-healing, anti-collagenase, anti-elastase, and antioxidant properties. However, its role in inhibiting elastase and collagenase enzymes, which are crucial for wound repair and skin regeneration, remains unexplored. This study evaluated the antioxidant properties, and elastase, collagenase, and hyaluronidase inhibitory activities of A. barbadensis gel extract in vitro, and by using molecular docking to understand the interaction mechanisms of key compounds with enzyme activity sites. The gel extract contained several active compounds, including phenolics, flavonoids, anthraquinones, and sterols, as determined via liquid chromatography connected to a hybrid ion trap and time-of-flight-mass spectrometry. Aloin A (47.54 ± 0.22 mg/g extract) and Aloin B (35.85 ± 0.17 mg/g extract) quantified via high-performance liquid chromatography were the main compounds in the gel extract. In this study, the antioxidant activity of gel extract was investigated using 2,2-Diphenyl-1-picrylhydrazyl (DPPH) and 2,2-Azino-bis-(3-ethylbenzo-thiazoline-6-sulfonic acid) (ABTS) assays. The gel extract showed better DPPH radical-scavenging activity than ABTS radical-scavenging activity. Particularly, the gel extract exhibited anticollagenase, anti-elastase, and anti-hyaluronidase activities with the half-maximal inhibitory concentrations (IC50) of 79.01 ± 0.11, 78.23 ± 0.07, and 87.31 ± 0.13 μg/ml, respectively. By molecular docking, aloins A and B derived from A. barbadensis gel extract have a strong affinity for elastase inhibition via the common amino acid HIS57. Moreover, non-cytotoxicity was observed in human fibroblasts treated with gel extract at concentrations ≤ 100 μg/ml. The IC50 value for cytotoxicity of the gel extract was more than 1,000 μg/ml. Treatment with the extract for 48 hours enhanced wound healing by inducing wound closure in a fibroblast scratch test. The wound-healing effects of the gel extract can be attributed to its antioxidant properties, which reduce oxidative stress, as well as its ability to inhibit elastase and collagenase, enzymes that degrade key proteins involved in skin regeneration. These results suggest that A. barbadensis gel extract is useful for application in human skin care and pharmaceutical products.
Keywords: Aloe barbadensis, anticollagenase, anti-elastase, anti-hyaluronidase, molecular docking